Beneficial effects of antitranspirants on water stress tolerance in maize under different plant densities in newly reclaimed land - Morsy, Ahmed Salah Mohamed (2023)
Number of leaves plant.−1 and leaf area index (LAI) The number of leaves plant−1 and LAI are important traits for plant growth and development. The data in Tables 2 and 3 showed that irrigation levels, plant densities, antitranspirants, and their interactions had a significant influence on the number of leaves per plant and LAI of maize in both seasons.